Acid Derivatives of Pyrazolo[1, 5-a]pyrimidine as Aldose Reductase Differential Inhibitors. Issue 11 (15th November 2018) - Balestri, Francesco; Quattrini, Luca; Coviello, Vito; Sartini, Stefania; Da Settimo, Federico; Cappiello, Mario; Moschini, Roberta; Del Corso, Antonella; Mura, Umberto; La Motta, Concettina
Summary: Aldose reductase (AKR1B1), the key enzyme of the polyol pathway, plays a crucial role in the development of long-term complications affecting diabetic patients. Nevertheless, the expedience of inhibiting this enzyme to treat diabetic complications has failed, due to the emergence of side effects from compounds under development. Actually AKR1B1 is a Janus-faced enzyme which, besides ruling the polyol pathway, takes part in the antioxidant defense mechanism of the body. In this work we report the evidence that a class of compounds, characterized by a pyrazolo[1, 5- a ]pyrimidine core and an ionizable fragment, modulates differently the catalytic activity of the enzyme, depending on the presence of specific substrates such as sugar, toxic aldehydes, and glutathione conjugates of toxic aldehydes. The study stands out as a systematic attempt to generate aldose reductase differential inhibitors (ARDIs) intended to target long-term diabetic complications while leaving unaltered the detoxifying role of the enzyme. Graphical Abstract: Highlights: Pyrazolopyrimidines behave as aldose reductase differential inhibitors They inhibit L-idose and GS-HNE reduction more efficiently than HNE reduction They may be useful candidates for a novel approach to treat diabetes complications Abstract : In this work, Balestri and co-authors provide the evidence that pyrazolopyrimidine derivatives are able to inhibit differently the catalytic activity of aldose reductase, depending on the presence of specific substrates. This finding opens up intriguing opportunities to target long-term diabetic complications while preserving the detoxifying role of the enzyme.